The effect of dancesport in psychological well-being of college students: chain mediation of perceived social support and study engagement - Chen, Zitong; Wang, Shuo; Jiang, Xianglong; Che, Tongtong; Shi, Yan (Frontiers in Psychology, 2025)
ObjectivePromoting the psychological well-being of college students is a critical issue in mental health education. While physical activity is known to enhance well-being, the specific mechanisms through which dancesport—an activity integrating sport, art, and social interaction—exerts its influence remain underexplored. This study investigates the chain mediation effect of perceived social support and study engagement in the relationship between dancesport participation and psychological well-being among college students.MethodsA cross-sectional study was conducted with 1,012 Chinese college students enrolled in dancesport courses. Participants completed self-report measures assessing dancesport participation, psychological well-being, perceived social support, and study engagement. Data were analyzed using structural equation modeling (SEM) and the SPSS PROCESS macro (Model 6) with 5,000 bootstrap samples to test the proposed chain mediation model.ResultsThe results indicated that: (1) Dancesport participation was significantly and positively associated with psychological well-being of college students: (β = 0.32, p < 0.001). (2) Perceived social support and study engagement play partial mediating roles between dancesport and psychological well-being, with indirect effects of 0.11 (95% CI [0.06, 0.17]) and 0.08 (95% CI [0.03, 0.13]), respectively. (3) A significant chain mediation pathway was identified: dancesport → perceived social support → study engagement → psychological well-being (indirect effect = 0.037, 95% CI [0.015, 0.062]).ConclusionThis study reveals that dancesport enhances college students’ psychological well-being not only directly but also indirectly by first fostering perceived social support, which in turn promotes greater study engagement. These findings underscore the multifaceted benefits of dancesport and provide a theoretical and practical basis for incorporating artistic and social physical activities into university mental health promotion programs.